Butyrate Suppresses Glucose Metabolism of Colorectal Cancer Cells via GPR109a-AKT Signaling Pathway and Enhances Chemotherapy - Geng, Hong-Wei; Yin, Feng-Yi; Zhang, Zhi-Fa; Gong, Xu; Yang, Yun (Frontiers in Molecular Biosciences, 2021)
Glycolysis inhibitors are promising therapeutic drugs for tumor treatment, which target the uniquely elevated glucose metabolism of cancer cells. Butyrate is a critical product of beneficial microbes in the colon, which exerts extraordinary anti-cancer activities. In particular, butyrate shows biased inhibitory effects on the cell growth of cancerous colonocytes, whereas it is the major energy source for normal colonocytes. Besides its roles as the histone deacetylases (HDACs) inhibitor and the ligand for G-protein coupled receptor (GPR) 109a, the influence of butyrate on the glucose metabolism of cancerous colonocytes and the underlying molecular mechanism are not fully understood. Here, we show that butyrate markedly inhibited glucose transport and glycolysis of colorectal cancer cells, through reducing the abundance of membrane GLUT1 and cytoplasmic G6PD, which was regulated by the GPR109a-AKT signaling pathway. Moreover, butyrate significantly promoted the chemotherapeutical efficacy of 5-fluorouracil (5-FU) on cancerous colonocytes, with exacerbated impairment of DNA synthesis efficiency. Our findings provide useful information to better understand the molecular basis for the impact of butyrate on the glucose metabolism of colorectal cancer cells, which would promote the development of beneficial metabolites of gut microbiota as therapeutical or adjuvant anti-cancer drugs.